Comparing three underwater trajectories of the swimming start - Tor, E.; Pease, D. L.; Ball, K. A. (Journal of Science and Medicine in Sport, 2015)
Once a swimmer enters the water they will not increase velocity, instead they will decelerate. One factor that will influence the velocity maintained during the underwater phase is the trajectory the swimmer adopts. Objectives: Once a swimmer enters the water they will not increase velocity, instead they will decelerate. One factor that will influence the velocity maintained during the underwater phase is the trajectory the swimmer adopts. This study aimed to identify how different underwater trajectories affect start time in elite swimmers. Methods: Fourteen swimmers performed three dives: a shallow dive with little underwater time (Dive 1), a flatter dive with intermediate time underwater (Dive 2) and a deep dive with lengthy underwater time (Dive 3). The proprietary `Wetplate` analysis system was used to collect performance time (time to 15 m) and other dive parameters. Results: A mixed modelling approach found Dive 1 was significantly slower than Dive 2 and 3 (time to 15 m). This indicated that both a shallow or deep dive slowed overall performance, with shallower dives adversely affecting performance the most. Conclusions: On average, using a flatter trajectory with a maximum depth of -0.92 ± 0.16 m similar to Dive 2 may prove to be beneficial to start performance. More research is needed to examine the interaction between drag and depth for individual swimmers to better understand the mechanisms influencing these findings and to further explore the notion of an ideal underwater trajectory.